PENERAPAN PROGRAM BADAN USAHA MILIK DESA (BUMDES) DALAM PENGELOLAAN POTENSI DAN SUMBER DAYA - Irgi Nazri Adlani (Jurnal Caraka Prabu, 2017)
Sindang Jaya Village Government established BUMDes as a motor of economic driving in rural areas through Bumdes program that has been made because through Bumdes facility ordinary people get capital for entrepreneurship and more independent in managing the potential of natural resources in Sindangjaya Village but in its formation is still minimal coaching from Local Government so that some problems arise, such as how the content of Bumdes program, and how its implementation as well as bagamanakah obstacles in managing the potential of village sindangjaya.Hasil research shows that the contents of the program Bumdes Sindang Jaya village is engaged in the type of business Social Business, Business Leasing Business Save Borrow other than that the implementation of BUMDes programs have been running well and Barriers in managing Bumdes and managing the potential Village natural resources on financial planning and agricultural products have not been well managed and proper target so that even though the program is already running but its content is not fully commonly felt by all people because of lack of knowledge in marketing the existing natural resources.